Challenges to library service [soundrecording] some current problems and responses - Bogue, Donald J. (Development Digest premier series, 1974)
Deals with predictions on population trends and suggests opportunities for librarians to extend service to previously elusive segments of the population. It describes the CLEP program for the educationally disadvantaged and encourages librarians to service outsiders to academic programs and to face related social problems.